Keputusan Investasi dan Kebijakan Dividen dengan Profitabilitas Sebagai Moderasi dalam Mempengaruhi Nilai Perusahaan pada Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia - Muhamad Imam Rusdi; Risal Rinofah; Alfiatul Maulida (Universitas 45 Surabaya, 2024)
This study aims to determine the effect of investment decisions and dividend policy with profitability as moderation in affecting the value of the company. This study is a quantitative study in which the data is processed with SPSS 25. The population in this study is a manufacturing company that is listed and publishes financial statements on the Indonesia Stock Exchange during the period 2019 to 2023. Determination of samples using purposive sampling method. In this study there are 80 samples of companies. This study used Moderated Regression analysis (MRA). The results showed that (1) investment decisions affect the value of the Company, (2) dividend policy affects the value of the Company, (3) profitability is not able to moderate investment decisions on the value of the Company, (4) profitability is able to moderate the dividend policy on the value of the company, (5) investment decisions and dividend policy simultaneously affect the value of the company.